Past Behaviour, Conscientiousness Personality, and Attitude Toward Engagement in Workplace Affair - Muhammad Irfan Syaebani; Alma Madina; Melia Retno Astrini (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2020)
The phenomenon of workplace romance is an integral part of organisational dynamics. Workplace romance might result in both positive and negative effect. The negative side of workplace romance bears the phenomenon of workplace affair, in which workers engage in extra-marital relations with each other. This research aims to test whether past behaviour, conscientiousness personality, which a part of big five model personality traits and attitude have an impact on the likelihood of employee’s engagement in the workplace affair. As many as 250 workers in Greater Jakarta participated in the survey with minimum tenure six months as criteria of sampling. The analysis of data is performed using structural equation modelling (SEM) process. The result indicates that workers who have workplace romance engagement in their past behaviour would affect the attitude of perceiving workplace romance. The attitude itself plays as a mediator between past behaviour and the engagement of workplace affair. At the same time, personality determinant does not give any significant effect on attitude and engagement in workplace affair. To mitigate the issue of workplace affair, the organisation needs to perform background checking prior accepting the employees since the past behaviour of engagement in workplace romance is the reliable indicator of future likelihood in workplace affair engagement. While the previous research studies about the effect of workplace romance, this study emphasize deeper into the findings from the workplace affair perspectives, which is the negative effect of workplace romance.Keywords: Workplace romance, Workplace affair, Attitude, Past behaviour, Conscientiousness* Faculty of Economics and Business, Universitas Indonesia, Jl. Prof. DR. Sumitro Djojohadikusumo, Kukusan, Kecamatan Beji, Kota Depok, Jawa Barat 16424, Indonesia** Tilburg School of Economics and Management, 5037 AB Tilburg, Netherlands https://doi.org/10.21632/irjbs.13.3.249-267